mRNA-Based Genetic Reprogramming - Warren, Luigi; Lin, Cory (Molecular therapy, 2019)
The discovery that ordinary skin cells can be turned into pluripotent stem cells by the forced expression of defined factors has raised hopes that personalized regenerative treatments based on immunologically compatible material derived from a patient's own cells might be realized in the not-too-distant future. A major barrier to the clinical use of induced pluripotent stem cells (iPSCs) was initially presented by the need to employ integrating viral vectors to express the factors that induce an embryonic gene expression profile, which entails potentially oncogenic alteration of the normal genome. Several "non-integrating" reprogramming systems have been developed over the last decade to address this problem. Among these techniques, mRNA reprogramming is the most unambiguously "footprint-free," most productive, and perhaps the best suited to clinical production of stem cells. Herein, we discuss the origins of the mRNA-based reprogramming system, its benefits and drawbacks, recent technical improvements that simplify its application, and the status of current efforts to industrialize this approach to mass-produce human stem cells for the clinic.